Experienced of thermal fatigue failure on closed blowdown system line in delay coker unit - Awang Ahmad, Mohd Zainuddin; Yob, Mohd Shukri; Mat Tahir, Noor Ayuma; Abd Latif, M.J. (2023)
Delay coker is one of the most important and profitable units in a refinery plant which consists of a closed blowdown system that is designed to contain blowdown from coke drums to quench tower. Due to constant used at various temperature, pressure, and conditions, components are susceptible to various of failures including thermal fatigue, corrosion, and others. Due to cyclic temperature, multiple cracks have been observed on the closed blowdown system (CBS) header piping in a short period. The crack was observed on the welding join between two different thickness pipes. This paper aims to study the structural integrity and risk level of the CBS line with the presence of different thickness intersection. Finite element analysis (FEA) was conducted on this line to evaluate the overall material behaviour and assessed the risk of failure. The acceptance criteria of the analysis were set to be based on ASME VIII-Division 2 part 5.2.2 (elastic stress analysis method) and ASME II-part D. Findings from FEA show that the failure occurred on the CBS line was caused by the presence of the different